Behavior of activated carbons by compound modification in high gravity for toluene adsorption - Qiang Guo; You-Zhi Liu; Gui-Sheng Qi; Wei-Zhou Jiao (Adsorption Science & Technology)
The rotating packed bed is a chemical apparatus that strengthens mass transfer between phases to enhance their reactivity. It can be used to modify adsorbent materials, greatly improving their chemical properties. This article studies the effect of compound modification of activated carbons in a high-gravity environment on their toluene adsorption. The compound modification includes physical (N 2 ) and chemical modification (HNO 3 ), and the effect of modification is compared between traditional fixed-bed and rotating packed bed modification. The physical characteristics of the activated carbons, including pore size, specific surface area, and morphology are tested by Brunauer–Emmett–Teller and scanning electron microscopy, and the surface functional groups of the activated carbons are determined by Fourier transform infrared spectroscopy and Boehm titration. The results indicate that the activated carbons modified by rotating packed bed have a larger specific surface area (871.5 m 2 /g) and smaller pore size (0.524 nm), and the content of acidic oxygen-containing groups is 1.5 times that of unmodified activated carbons. The adsorption capacity of the activated carbons compound-modified by rotating packed bed increases by 69% compared with the unmodified activated carbons. The adsorption by the rotating packed bed-compound-modified activated carbons obeys the Freundlich model. The modification of activated carbons by rotating packed bed greatly enhances their specific surface area, pore size, and surface content of oxygen-containing functional groups, markedly improving the adsorption performance and increasing the utilization rate.